Geometric algebra for computer science : an object-oriented approach to geometry - Dorst, Leo, 1958- (Morgan Kaufmann series in computer graphics., 2007)
Within the last decade, Geometric Algebra (GA) has emerged as a powerful alternative to classical matrix algebra as a comprehensive conceptual language and computational system for computer science. This book will serve as a standard introduction and reference to the subject for students and experts alike. As a textbook, it provides a thorough grounding in the fundamentals of GA, with many illustrations, exercises and applications. Experts will delight in the refreshing perspective GA gives to every topic, large and small.-David Hestenes, Distinguished research Professor, Department of Phy.